A Psycho-Spiritual Approach to Purpose-Based Career Coaching: A Step-By-Step Guide for Practitioners - Otu, Mkpoikanke Sunday; Eseadi, Chiedu (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Life is meaningless, drowsy, stressful, boring, wasteful, and fruitless without purpose. Hence, purpose justifies someone’s existence on earth. It is assumed therefore that nobody was born by accident. The Creator, God thought about it and decided that it was good for one to be born. It is therefore one’s responsibility to find the reasons that justify one’s existence on earth and choose a career that corresponds with it. The main purpose of this article was to explore the steps for implementing purpose-based career coaching. The study was a mixed method research aiming to explore the experiences and perspectives of individuals about purpose-based career coaching. Participants included students, graduates, teachers, parents, counsellors, and lecturers. Data was generated through multiple methods, including individual interviews, focus groups, and qualitative surveys. Thematic analysis was employed to analyze the data and identify key themes. The findings of this study revealed three distinct themes: 12 steps guide for a purpose-based career coaching, the core beliefs underlying purpose-based coaching, and the objectives associated with purpose-based career coaching. With these themes in mind, practitioners can adopt a holistic approach when coaching individuals towards achieving their purpose-driven career goals. This structured approach to career coaching ensures a comprehensive and systematic exploration of the career-related challenges and opportunities that individuals may face. Throughout the article, attention is given to the integration of spirituality into the career development process. The implication of the article is that through the incorporation of spiritual principles and practices, individuals can tap into a deeper sense of purpose and direction which will in turn enable them to navigate their career journeys with clarity and confidence. In addition, the article offers helpful information and techniques to help people grow in their spiritual awareness and incorporate it into their work lives. Keywords: Career Coaching; Career Choice; Psycho-Spiritual; Purpose; Reimagining